Public intention to report child abuse in Malaysia: a cross sectional study / Nurul Hidayana Mohd Noor ... [et al.] - Ghazali, Sharifah Hanis Syamimi; Abu Bakar, Nurul Nabila Huda (Universiti Teknologi MARA, Kedah, 2021)
Child abuse is a prevailing problem for Malaysia and the evidence has shown that the reporting level is still low and most of the child abuse cases go unreported due to stigma and attitudes of most Malaysians (Ministry of Health Malaysia, 2020). Thus, this study aims to identify the factors associated with public' intention to report child abuse by testing a hypothetical model and (2) to investigate the significant predictor on with public' intention to report child abuse. A convenience sample of 252 respondents was used. The research instruments were adapted from Child Abuse Report Intention Scale (CARIS) and the results of Pearson correlation and multiple regression were presented. Our finding first discovered that attitude (r = -0.380, p = 0.000), subjective norm (r = 0.410, p = 0.000), and perceived behavioural control (r = 0.440, p = 0.000) were significantly associated with the intention to report child abuse. Second, subjective norm emerges as the strongest predictor towards intention to report for child abuse (β= 0.36, p=0.000). Research and managerial implications are provided.